Particle size effects on coarse soil-geogrid interface response in cyclic and post-cyclic direct shear tests. Issue 6 (December 2016) - Wang, J.; Liu, F.Y.; Wang, P.; Cai, Y.Q.
Abstract: The interface shear behavior of soil against geosynthetic is important in the design of geosynthetic-reinforced soil structures. This study involves the use of a series of Monotonic Direct Shear (MDS) tests, Cyclic Direct Shear (CDS) tests and Post-cyclic Direct Shear (PCDS) tests to investigate the coarse silica soil-geogrid interface monotonic and cyclic shear behavior. In particular, the influence of cyclic shear on the interface monotonic behavior is analyzed in detail. The effect of soil particle size on interface cyclic and post-cyclic shear behavior is examined and discussed. The results indicate that in cyclic direct shear, the interfaces exhibit cyclic hardening, the interface damping ratio decreased with increasing cycle number and soil relative density, and an interface with a larger particle size has a higher contraction value. In the monotonic condition, the shear stress–displacement curves exhibit post-peak strain softening behavior, and the apparent adhesion and friction angle at the interface both increased with increasing soil particle size. Cyclic shear increased the apparent adhesion at the interface and intensified the soil dilatancy.